2018
DOI: 10.1088/1361-6382/aab97b
|View full text |Cite
|
Sign up to set email alerts
|

The Gross–Pitaevskii equations of a static and spherically symmetric condensate of gravitons

Abstract: In this paper we consider the Dvali and Gómez assumption that the end state of a gravitational collapse is a Bose-Einstein condensate of gravitons. We then construct the two Gross-Pitaevskii equations for a static and spherically symmetric configuration of the condensate. These two equations correspond to the constrained minimisation of the gravitational Hamiltonian with respect to the redshift and the Newtonian potential, per given number of gravitons. We find that the effective geometry of the condensate is … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…The nature of the corresponding fine-grained description is yet unknown owing, of course, to the unavailability of a consistent quantum theory of gravity. Despite this, however, it may be possible to realize a mean field description of the gravitoncondensate picture of the black hole, say, in terms of an appropriate generalization of the Gross-Pitaevskii equation 62,63 . An interesting implication of this, which seems to have not been adequately appreciated previously, is that dynamics of the modes of perturbations of a black hole near the horizon must be described by an appropriate BdG-like equations, as opposed to, say, Eq.…”
Section: Possibility Of a New Kind Of Gravitational Echomentioning
confidence: 99%
“…The nature of the corresponding fine-grained description is yet unknown owing, of course, to the unavailability of a consistent quantum theory of gravity. Despite this, however, it may be possible to realize a mean field description of the gravitoncondensate picture of the black hole, say, in terms of an appropriate generalization of the Gross-Pitaevskii equation 62,63 . An interesting implication of this, which seems to have not been adequately appreciated previously, is that dynamics of the modes of perturbations of a black hole near the horizon must be described by an appropriate BdG-like equations, as opposed to, say, Eq.…”
Section: Possibility Of a New Kind Of Gravitational Echomentioning
confidence: 99%
“…By means of a binding potential, these constituents can superimpose in one particular quantum state, effectively making the compact object a self-gravitating Bose-Einstein condensate (BEC) [26][27][28][29][30][31][32][33], at least to leading order of approximation. Moreover, the virtual gravitons are expected to be marginally bound in this potential well, giving rise to the so-called maximal packing relation…”
Section: Application To Non-singular Bhsmentioning
confidence: 99%
“…3, following Ref. [16], we will discuss a method to determine the size of the interior condensate and demonstrate that the generalization to the f (R) gravity again gives us richer results compared to the case of ordinary gravity. Then in Sec.…”
Section: Introductionmentioning
confidence: 98%
“…Working in the static spherically symmetric setup, Cunillera and Germani in Ref. [16] adapted the derivation of the Gross-Pitaevskii (GP) equation for ordinary BEC to this graviton condensate, namely by varying the condensate energy obtained from the Arnowitt-Deser-Misner (ADM) formalism while the number of gravitons is kept fixed. They found that the interior of the condensate is described by the dS spacetime while the exterior is described by the Schwarzschild spacetime, which is analogous to the picture of gravastar explained earlier.…”
Section: Introductionmentioning
confidence: 99%